4-(4-Methylbenzenesulfonamido)benzoic acid N,N-dimethylformamide monosolvate - Huang, Miao-Ling (International Union of Crystallography, 2011)
In the title compound, C(14)H(13)NO(4)S·C(3)H(7)NO, the C—S—N—C torsion angle of −64.55 (17)° defines the folded conformation of the molecule. The dihedral angle between the benzene rings is 83.367 (6)°. In a crystal, molecules are linked into a chain along a axis through intermolecular N—H⋯O and O—H⋯O hydrogen bonds. There is also an intramolecular C—H⋯π interaction.